Implementation Plan for Group Tutoring Services Using the Discussion Method to Increase Adjustment to School Regulations - Lora Oseli; Fitria Kasih; Rahmawati Wae (Jurnal Counseling Care, 2024)
This reserach is motivated by the existence of the problem about self adjustment to the low rules of school. This research aims to descripbe: 1) Self adjustment overview of students to the rules of school. 2) Design of implementation of group guidance services by using discussion method in improving students’ self adjustment to the rules of school. This research is carried out by an analysis descriptive method. The population in this research is students at the grade of XI IIS 1 Senior High School 1 Lunang who are experiencing low self adjustment to the rules of school with a total of 12 students. The sampling using purposive sampling technique with a total is 8 students. The data collected by using questionnaire, then analyzed by using percentage classification. The result of this research discloses that: 1) Self adjustment overview of students to the rules of school, is the low category. 2) Design of implementation of group guidance services by using discussion methods in improving students’ self adjustment to the rules of school. Based on the result of this research, it is recommended for counselors to be able to implement group guidance services by using discussion methods to students at the grade of XI IIS 1 Senior High School 1 Lunang in improving self adjustment to the rules of school as it is designed in this research.